Prevalence of nosocomial infection in intensive care unit - a retrospective study - Santos, Reginaldo Passoni dos (2014)
Aim: To identify the prevalence of nosocomial infection in Intensive Care Unit for adults. Method: quantitative, descriptive and retrospective study performed by research in the records of the hospital infection control committee in a public hospital in a city of Paraná. The sample comprised all records for the period January to December 2012. Data analysis occurred using Microsoft Windows Excel® software, version 2010. Results: The prevalence of nosocomial infection was 27.35%, and Acinetobacter sp. (22.92%) was the most commonly identified pathogen. In terms of topography, we found that respiratory tract infections were the most frequent, occurring in 36.46% of cases. Conclusion: The data survey showed a median prevalence of nosocomial infection when compared to the provisions in the literature.